2018
DOI: 10.1186/s13063-018-2783-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small-dose remifentanil combined with index of consciousness monitoring on gastroscopic polypectomy: a prospective, randomized, single-blinded trial

Abstract: BackgroundWith the development of painless diagnosis and treatment, remifentanil, a synthetic opioid agonist, is increasingly used in gastroscopy for its rapid, short-term, and potent analgesic effect. However, the dosage of remifentanil used in endoscopy is unclear. Index of consciousness (IOC) is a new anesthesia depth-monitoring indicator that can be divided into index of consciousness 1 (IOC1) and index of consciousness 2 (IOC2); IOC1 is used for estimating a patient’s sedation state, whereas IOC2 reflects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For example, it is reported that IoC is a better predictor than BIS for representing patient's consciousness during the anesthesia induction and maintenance with sevoflurane and remifentanil. 32 Monitoring anesthesia through IoC makes the whole procedure more controllable and effectively reduces adverse events during the operation. 33 The current clinical research on IoC mainly focuses on IoC1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is reported that IoC is a better predictor than BIS for representing patient's consciousness during the anesthesia induction and maintenance with sevoflurane and remifentanil. 32 Monitoring anesthesia through IoC makes the whole procedure more controllable and effectively reduces adverse events during the operation. 33 The current clinical research on IoC mainly focuses on IoC1.…”
Section: Discussionmentioning
confidence: 99%
“…Tachycardia or bradycardia was defined as heart rate (HR) increased or decreased by more than 25% of the first recorded HR on the monitor screen ( 20 ) Urapidil (10–20 mg) or ephedrine (0.1–0.2 mg/kg) was administered IV to treat hypertension or hypotension, respectively. Esmolol (1 mg/kg) or atropine (0.005–0.01 mg/kg) was administered IV to treat tachycardia or bradycardia, respectively ( 16 , 21 ). Hypoxemia was defined as 75% < SpO 2 < 90% in 60 s or SpO 2 < 75% at any moment ( 20 , 22 ).…”
Section: Methodsmentioning
confidence: 99%